PENTINGNYA PERDA TRANSPARANSI DALAM MEWUJUDKAN GOOD GOVERNANCE DI KOTA BEKASI - ., Nuraina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2010)
This paper focuses on the importance of transparency to local regulations imposed in Bekasi City, as the manifest efforts of Good Governance. If these regulations apply will certainly help the development of construction in the Bekasi City as clean government, including the community that can support government programs in the strict sense. Therefore, through this paper is expected to open the eyes that local regulation of transparency is not a barrier for Bekasi’s local government performance, but instead